Visual field changes in normal pressure glaucoma and their association with risk factors - Kosior-Jarecka, Ewa; Wróbel-Dudzińska, Dominika; Łukasik, Urszula; Żarnowski, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Aim : To determine differences in visual field abnormalities in primary open angle glaucoma between patients with high and normal baseline intraocular pressure, and to assess whether some risk factors affect the defect pattern. Material and methods : The study group consisted of 170 patients with normal tension glaucoma and 125 patients with high tension glaucoma. The retrospective analysis of visual field, splinter hemorrhages, peripapillary atrophy, disc notches and vascular risk factors (low blood pressure, migraines and cold extremities) was carried out. Results : In patients with high tension glaucoma the most frequently observed scotoma were advanced changes (65.8%), arcuate scotoma (19.7%), paracentral scotoma (7.7%). Advanced changes were observed in 43.5% of patients with normal tension glaucoma, with arcuate scotoma seen in 28.7% and paracentral scotoma in 15.7% of them. The difference in visual field changes between both groups was statistically significant (p=0.003). The prevalence of disc hemorrhages was significantly higher in patients with normal tension glaucoma (16% vs. 4.3%, respectively). In patients with normal tension glaucoma and hemorrhages (DH+) the paracentral scotoma was seen more frequently (DH+ vs. DH-: 22.3% vs.10.2%). The type of scotoma in normal tension glaucoma was linked to the presence of cold distal extremities, which were seen more frequently in this group (p=0.000). Patients with normal tension glaucoma and cold extremities (CE+) typically presented with arcuate scotoma (CE+ vs. CE-: 27.8% vs. 0%). Peripapillary atrophy was more frequent in normal tension glaucoma and in males, and it was not linked to the type of scotoma (p= 0.133). Patient with high tension glaucoma and peripapillary atrophy had more often presented with advanced changes in visual field (p= 0.001). Conclusions : Scotoma morphology in primary open angle glaucoma depends on glaucoma subtype. Additionally, in normal tension glaucoma, it is related to the presence of disc hemorrhages and vascular risk factors.